Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Di Kantor Imigrasi Kelas I Non Tpi Depok - Nanda Alifah Sugiarto (CV. ALIM'SPUBLISHING, 2023)
Employee motivation and discipline play an important role in increasing the efficiency and effectiveness of a company. An employee who has high discipline and motivation will be able to carry out his duties properly and optimally, so that the company's employee performance targets can be achieved. This study aims to examine the correlation between individual motivational factors and employee discipline on employee performance by using the SPSS version 25 program at the Immigration Office Class I Non Tpi Depok. Existing data in this study were taken using the method of documentation, observation, distribution of questionnaires or questionnaires, and interviews. This study uses a quantitative method because it focuses on measurements and samples to test variables and hypotheses. Several tests were carried out using the SPSS program, including the Validity Test, Earnings Test, Normality Test, Multicollinearity Union, Heteroscedasticity Test, Autocorrelation Test, Correlation Coefficient, Determination Coefficient, Multiple Linear Regression Coefficient, T Test, and F Test. The results of the tests This shows that there is a positive relationship between motivation and work discipline on employee performance at the Immigration Office Class I Non TPI Depok.